CAS-Plan: Civitas Academic of School - Differentiated Learning to Optimize Science Learning Oriented to Increasing Scientific Literacy in Class VII-B of SMP IT Ar Raihan Bandar Lampung - Prayoga, Angga; Romli, Sunaryo; Agustiawan, Agustiawan; Yusuf, Eka Yustian; Misuri, Misuri (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
This research aims to determine the effectiveness of using CAS-Plan to improve students' scientific literacy skills in science learning. This Classroom Action Research was carried out on students in class VII-B SMP IT Ar Raihan Bandar Lampung which consisted of 24 students. Data on mastery of scientific literacy was collected using scientific literacy test instruments using test instruments that have been tested for validity, and reliability and have good distinguishing power. PTK is carried out in 2 cycles. In each cycle, there are two learning meetings. This research is declared successful if it meets all the specified criteria, namely (1) the student's scientific literacy test results increase from the previous cycle, (2) the student's mastery of scientific literacy skills is ≥ 75, class completion reaches ≥ 85% and the average score class ≥ 80. The results showed that 9 out of 24 students completed the scientific literacy of students before the action (pre-cycle) (37.5%), the class average was 58.0. After the action was taken, the results of the scientific literacy test showed that 22 students had completed it (91.6%), with a class average of 87.5. So, based on the research results, it can be concluded that the use of CAS-Plan in science learning has proven effective in increasing students' scientific literacy.